2019
DOI: 10.1021/acs.organomet.9b00034
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Multiple Coordination Modes in Silyl-Bridged Bis(phosphinine) Complexes

Abstract: The bis(phosphinine) [bis{3-methyl-6-(trimethylsilyl)phosphinine-2-yl}dimethylsilane] (1) was synthesized and its coordination chemistry explored. Molybdenum and chromium carbonyl complexes were crystallographically characterized featuring 1 bound η 6 through one phosphinine [Mo(CO) 3 (η 6 -1)] (2Mo), η 6 through both phosphinines to two metal centers [{M(CO) 3 } 2 (μ-η 6 :η 6 -1)] (3M 2 , M = Cr, Mo), and chelating with η 1 coordination through both phosphines [M(CO) 4 (κ:η 1 :η 1 -1)] (4M, M = Cr, Mo). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…1 H NMR spectroscopy revealed 2 multiplets for the H atoms at the 4-and 5-positions along with 1 resonance for the 3-Me group and 1 SiMe 3 environment in agreement with a plane of symmetry passing through the palladium and the SiMe 2 group. However, the presence of two resonances for the SiMe 2 group indicated that the ligand was not coplanar with the PdCl 2 fragment, as has been seen previously in complexes of this ligand with other metal fragments [58]. We attributed this flexibility to bind to metals out of the plane of the ligand to the high s-character of the phosphinine lone pairs, which render them less directional [11].…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…1 H NMR spectroscopy revealed 2 multiplets for the H atoms at the 4-and 5-positions along with 1 resonance for the 3-Me group and 1 SiMe 3 environment in agreement with a plane of symmetry passing through the palladium and the SiMe 2 group. However, the presence of two resonances for the SiMe 2 group indicated that the ligand was not coplanar with the PdCl 2 fragment, as has been seen previously in complexes of this ligand with other metal fragments [58]. We attributed this flexibility to bind to metals out of the plane of the ligand to the high s-character of the phosphinine lone pairs, which render them less directional [11].…”
Section: Resultssupporting
confidence: 58%
“…Other related examples are cationic and supported by a β-diketiminate framework [56,57]. The phosphinines 4 [58], 5 [36] and 6 [18] all featured additional P donors, either another phosphinine ring (4) or PPh 2 moieties. They were synthesised by the reaction of diazaphosphinine (3) with alkynes in two sequential steps due to the slower reaction of the intermediate azaphosphinines with alkynes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While pyridines belong to the core area of heteroaromatic chemistry, phosphinines (also coined phosphabenzenes) have a much shorter history . However, their molecular properties, e.g., in comparison to pyridines, in homogeneous catalysis and coordination chemistry, , have stirred significant work over recent decades toward their synthesis and functionalization Scheme , top).…”
Section: Introductionmentioning
confidence: 99%
“…46,51 Ruthenium hydrides are implicated in many catalytic reactions, yet the first Ru complex comprising of both a hydride and phosphinine ligand has only been described recently by us. 52 Herein, we describe the first ruthenium phosphinine dihydride complex and compare its catalytic activity to that of classical diphosphine-supported complexes for AD reactions.…”
mentioning
confidence: 99%